Effect of Some Plant Extracts of Leaves of Cassia acutifolia on Growth and Activity of Candida albicans isolated from clinical cases of Candidasis - Hayfa’a A. Yousif; Mahdi T. Al-Kaisy; Asia N. Al-Hachami (Journal of Madenat Alelem University College, 2016)
The study was conducted to evaluate the antimicrobial activity of aqueous and ethanolic extracts (cold and hot) extracted from leaves of Cassia acutifolia against Candida albicans isolated from clinical cases. Twenty five isolates of yeast were isolated from different cases of candidiasis. Four isolates that isolated from vagina, intertriginous, nail, mouth and standard isolate were used in further experiments. Results of the sensitivity of C. albicans towards nystatin showed that minimum inhibitory concentration (MIC) for all isolates was 0.15 mg/ ml. Analysis of crude extracts of leaves of C. acutifolia was carried out to determine its contents from biologically active compounds were isolated from extract, results of sensitivity of the isolates of C. albicans towards crude extracts showed that the cold alcoholic extract from the leaves of C. acutifolia showed high inhibitory effect on growth of the isolates of C. albicans. The isolates that isolated from intertriginous and vaginal showed sensitivity to cold alcoholic extract that extracted from leaves of C. acutifolia at MIC 30 mg/ ml to both isolates. Cold alcoholic extract from leaves of C. acutifolia showed high effect on the percentage of germ tube formation which is one of virulent factors of C. albicans so there is a reducing in the percentage of germ tube formation by increasing the concentration of extract especially for vaginal and standard isolates during incubation period of 2-6 hrs.